The effects of exercise on VO2peak, quality of life and hospitalization in heart failure patients: A systematic review with meta-analyses. Issue 9 (2nd September 2021) - Dallas, Konstantinos; Dinas, Petros C.; Chryssanthopoulos, Costas; Dallas, George; Maridaki, Maria; Koutsilieris, Michael; Philippou, Anastassios
Abstract: Exercise training has become one of the most fundamental components of cardiac rehabilitation. This systematic review with meta-analyses has the objective to determine the effectiveness of exercise on selected cardiac rehabilitation outcomes, i.e. peak oxygen consumption (VO2 peak), hospitalization and quality of life (QOL) of patients with heart failure. PubMed, EMBASE, and Cochrane Library were searched up to May 2019 to identify randomized controlled trials comparing exercise training to usual care. Overall, 131 trials were included with a total of 9, 761 patients, the majority of whom were males (74%), predominantly with reduced ejection fraction and NYHA class ranging from II to III. There was a significant improvement in VO2 peak in the exercise group compared to non-exercise control group (mean difference: 2.98 mL/kg/ min, 95% CI: 2.52–3.43, p  < 0.001; 84 RCTs, n = 3, 690 patients). Exercise training was also beneficial for the patients' QOL. The QOL meta-analysis included 5, 786 patients and showed a clinically significant improvement of QOL following exercise (−0.82, 95% CI: −1.02 to −0.62; p  = 0.00001; I 2  = 91%). Hospitalization incidence of heart failure patients was also lower in the exercise compared to control group (fixed-effect Odds Ratio: 0.56, 95% CI: 0.42–0.75, p  < 0.0001; 26 trials, 4, 664 participants). Exercise-based rehabilitation improves V02 peak and QOL and reduces the incidence of hospitalization of heart failure patients.